The Development and Formation of the Institution of a School Counselor in American High Schools in the Process of Career Development of Students - Hurman, Tetyana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article focuses on the development and formation of the institution of a school counselor during the process of career development of students. The transformation of terms “vocational guidance” and “career counseling” is being investigated. The preparation of school counselors in higher education establishments of the USA is in the focus. The article analyzes some programs, national standards and some models. They outline accurately the duties and functions of school counselors. It is characterized the main principles of the activity of school counselors. The main directions of their work, the distribution of their time are shown, which prove the necessity and effectiveness of their activity